HUBUNGAN DISIPLIN DENGAN KINERJA GURU STUDI KASUS DI SMA NEGERI DI 3 KECAMATAN KOTA DEPOK - Wulan, Sarah (Jurnal Ilmiah Widya, 2013)
Job performance is formally defined as the value of the set of employee behaviors that contribute to organizational goal accomplishment. Performance is important in management because it is related to the productivity of the institution or organization. Teacher performance is determined by several factors such as discipline. This study aims to determine: the relationship between the disciplines with the performance of teachers. The research was conducted on the state senior high schools in three districts of Depok, West Java. The method used was survey. The target population was 109 of the teachers with the State Civil Service status. The number of whole sample is 86 teachers. The instrument used is questioner. The results of research found that: (1) there is a positive relationship between the disciplines with performance of teachers. The better the teacher’s discipline, the higher the performance of teacher will be. (2) The principals as managers and leaders have an important role to improve teacher performance. (3) There are still teachers who have a lack of discipline that affect performance.